1983
DOI: 10.1084/jem.157.2.705
|View full text |Cite
|
Sign up to set email alerts
|

Clonotypic structures involved in antigen-specific human T cell function. Relationship to the T3 molecular complex.

Abstract: Multiple lineage-specific surface molecules have recently been defined on human T lymphocytes. Although some of these appear during late intrathymic ontogeny and are maintained on all peripheral T cells (T3), others (T4, TS) arise earlier in differentiation and are selectively expressed on functional subpopulations of human T lymphocytes (1-3). In the case of the 20,000-mol wt T3 surface molecule, both its appearance in intrathymic ontogeny at the time of acquisition of immunologic competence (1, 4) and its cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
219
0
3

Year Published

1985
1985
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 796 publications
(237 citation statements)
references
References 52 publications
15
219
0
3
Order By: Relevance
“…Thus, the in vitro cell population should have reflected, as closely as possible, the cells that are likely to encounter antigen in vivo. Moreover, anti-T3 was selected as the initial activating ligand since it is now known (24,25) that antigens activate T cells via interaction with a 90 kD disulfide-linked heterodimer noncovalently associated with three smaller proteins on the cell surface, the Ti-T3 complex. By using mAb reactive specifically with T3, we hoped to activate all mature T4 + and T8 + cells and at the same time avoid stimulation of other surface structures that might affect the resulting IL-2-promoted response.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the in vitro cell population should have reflected, as closely as possible, the cells that are likely to encounter antigen in vivo. Moreover, anti-T3 was selected as the initial activating ligand since it is now known (24,25) that antigens activate T cells via interaction with a 90 kD disulfide-linked heterodimer noncovalently associated with three smaller proteins on the cell surface, the Ti-T3 complex. By using mAb reactive specifically with T3, we hoped to activate all mature T4 + and T8 + cells and at the same time avoid stimulation of other surface structures that might affect the resulting IL-2-promoted response.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies in the 1970s claiming that certain immunoglobulin isotypes were associated uniquely with T cells (IgT) proved irreproducible, confusing, and incorrect. Finally, in 1982-3, several groups generated clonotypic antibodies against various T cell hybridomas and tumors [27][28][29][30][31]. These antibodies permitted a long awaited biochemical analysis of the putative TCR, which revealed a heterodimeric receptor with both constant and variable regions, similar to the immunoglobulin molecule.…”
Section: The Enlightenmentmentioning
confidence: 99%
“…As shown in Table 3, all clones lysed NK-sensitive K562 eells, indieating tbat CD4-CD8-TCRa/?+ T cells bave MHC-unrestricted cytotoxic activity in addition to helper activity for immunoglobulin production by B cells. It has been shown that CD3/TCR eomplex is essential for the mediation of antigen-specific cytotoxicity in both CD4' and CD8+ cytotoxic T lymphocytes (CTL), based on the findings that CD3 or anti-TCR MoAb inhibited tbeir cytotoxicity (Landegren et at., 1982;Meuer et al, 1982;Meuer et al, 1983). Moreover, MHCunrestricted cytotoxicity mediated by both CD4+ and CD8+ CTL was found to be inhibited also by CD3 MoAb in most eases (Tbiele & Lipsky, 1989).…”
Section: Cytotoxic Activity Of Clonesmentioning
confidence: 99%